2006
DOI: 10.1590/s0100-204x2006001200009
|View full text |Cite
|
Sign up to set email alerts
|

Fungos micorrízicos no crescimento e na extração de metais pesados pela braquiária em solo contaminado

Abstract: Resumo -Avaliou-se, em casa de vegetação, a influência de 14 isolados de fungos micorrízicos arbusculares (FMA) Mycorrhizal fungi influence on brachiariagrass growth and heavy metal extraction in a contaminated soilAbstract -The influence of 14 arbuscular mycorrhiza fungal isolates (AMF) on brachiariagrass growth and extraction of Zn, Cd, Cu and Pb from a contaminated soil was evaluated in a greenhouse experiment. Mycorrhizal and nonmycorrhizal Brachiaria decumbens plants were grown in pots with 0.92 kg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 27 publications
0
8
0
9
Order By: Relevance
“…The extraction rate of Pb and Cr is limited by low inherent solubility (Nascimento & Xing, 2006). Silva et al (2006) found that elevated soil concentrations of Pb did not increase its concentration in the aerial portion of B. decumbens, which confirms the low bioavailability of Pb in soils. Nevertheless, roots may absorb Pb and store it in cell walls; its translocation from roots to aerial portions is limited.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The extraction rate of Pb and Cr is limited by low inherent solubility (Nascimento & Xing, 2006). Silva et al (2006) found that elevated soil concentrations of Pb did not increase its concentration in the aerial portion of B. decumbens, which confirms the low bioavailability of Pb in soils. Nevertheless, roots may absorb Pb and store it in cell walls; its translocation from roots to aerial portions is limited.…”
Section: Resultsmentioning
confidence: 80%
“…Its concentration is usually higher in roots, but it may be translocated to the aerial portion of plants if present in excessive amounts (Kabata-Pendias & Pendias, 1992). Silva et al (2006) evaluated the growth of Brachiaria decumbens and its extraction capacity of Zn, Cd, Cu, and Pb from a contaminated soil, in greenhouse conditions and inoculated or not with arbuscular mycorrhizal fungi. In plants without arbuscular mycorrhizal fungi the mean Zn content was 1,511 mg kg -1 in dry matter within the aerial portion -a value quite above the toxic level for these plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentro da fitorremediação, a capacidade das plantas em extrair os metais do solo e acumulá-los preferencialmente na parte aérea, é denominada fitoextração (Nascimento e Xing, 2006). Embora, a avaliação da tolerância e a capacidade de extração de metais por diferentes espécies de plantas tenham sido intensificadas (Jiang et al, 2004;Silva et al, 2006;Xia e Shen, 2007;Wang et al, 2009;Santos et al, 2010), ainda existe a necessidade de ampliar o conjunto de espécies avaliadas para o emprego em programas de fitorremediação de Cu. Nesse contexto, devido à maior facilidade de propagação e cultivo, seria importante que as plantas cultivadas em áreas agrícolas fossem avaliadas quanto ao grau de tolerância e como possíveis candidatas à fitoextração de metais pesados.…”
Section: Introductionunclassified
“…Por esse motivo, o uso da fitorremediação, tecnologia baseada no uso de plantas capazes de absorver e acumular em seus tecidos metais pesados e outros compostos químicos do solo e da água, ganhou grande interesse durante as últimas década (Maine et al, 2004;Silva et al, 2006;Skinner et al, 2007;Agunbiade et al, 2009).…”
unclassified